Nurses' attitudes towards support for and communication about sexual health—A qualitative study from the perspectives of oncological nurses - Annerstedt, Catharina Frid; Glasdam, Stinne (Journal of clinical nursing, 2019)
Aim and objectives To explore nurses' articulations of support and communication regarding sexual health with patients. Background Sexual health is adversely effected by cancer and various oncological treatments. Patients' often have the experience that healthcare professionals do not talk about sexual health. Method Semi‐structured interviews were conducted with seven nurses in Southern Sweden. Content analyses were made, inspired by Foucault's concepts of power, discipline and normalisation. SRQR checklist was used. Results Patients' sexual health had low priority in the oncological clinic from the perspective of nurses. The medical logic directed nurses' articulations about sexual health towards a physical view, understood as sex, and sexual problems, which could be treated pharmacologically. Further, nurses articulated a sexual norm that sex belongs to young people and younger persons in permanent, monogamous and heterosexual relationships. This norm‐governed nurses' inclusion and exclusion of patients in communication about sexual health. According to nurses, most patients did not mention sex, but some patients challenged the clinic's norms. Assessing sexual health problems, nurses often engaged other professions and thereby became gatekeepers for patients' options for getting help. Conclusions From the perspective of nurses, nurses' support and communication regarding sexual health with patients with cancer diagnosis were relatively absent and had a low priority in an oncological clinic. Overall, the nurses had the power to set the agenda about patients' sexual health in the oncological clinic. The clinical gaze became a disciplinary technique that tacitly defined by whom, in what way and how sexual health could be articulated in an oncological clinic. Relevance to clinical practice By illuminating nurses' preconceptions, thoughts and actions in relation to cancer patients' sexual health, the results invite practitioners to reflect upon and discuss the challenges, opportunities and limitations in providing inclusive and supportive sexual health care to cancer patients.